(untitled) (Innovative professional education, 2024)
Today, it is clear to most people that without civilized entrepreneurship, Ukraine cannot create a powerful economy, cannot enter the world markets of goods and services. For many citizens, entrepreneurship is becoming the main type of work. The young generation feels the greatest urge to run their own business, the importance of starting their own business, therefore it is especially important to ensure high-quality training of students of the system of professional (vocational and technical) education for entrepreneurial activity, to promote professional formation, the formation of entrepreneurship, and to strengthen motivation for self-development through the use of ViAL+ business simulation